Conhecimento Organizacional na Polícia Federal: um Estudo do Curso de Especialização em Ciências Policiais - Mota, Jacques Douglas (2021)
Introduction: Currently, the police work under the paradigm of scientific knowledge, the result of the development of professionalization processes based on the selection and training of its members. As a result, police corporations created their own structures for the circulation of organizational knowledge in order to prepare themselves for changes in the scenarios in which they operate. Context: in the case of the Federal Police, the research observed that the specialization course in Police Science can be an important component in organizational knowledge management. Problem: the study sought to understand how the specialization course in Police Science offered by the National Police Academy contributes as a component of organizational knowledge management in the Federal Police. General objective: the research analyzed how the specialization course in Police Science offered by the National Police Academy contributes as a component of organizational knowledge management in the Federal Police. Theoretical foundation: the investigation had its approach based on Nonaka and Takeuchi's theory of knowledge creation (1995), which presents ontological elements - individual, group, organization, interorganization - and epistemological - tacit knowledge and explicit knowledge, and the four phases that knowledge runs in this process: socialization, externalization, combination and internalization. Methods and procedures: bibliographical, documental and field research were used as methods and procedures. Approach: qualitative and quantitative descriptive character. Search Type: descriptive search. Data collection instrument: semi-structured questionnaire applied to twenty-three graduates of the specialization course in Police Science. The instrument aimed at diagnosing the specialization course in Police Sciences as a component of organizational knowledge management in relation to the creation and sharing of generated knowledge. Method of data treatment: the study of the data was carried out through a survey of the categories listed, with content analysis in a qualitative and quantitative way. Main results found: the research found that the Federal Police has a modern and current institutional development plan, maintaining alignment of its concrete actions with these proposals, however, the processes and components implemented by the institution in the management of knowledge generated in the specialization course in Police Science must be perfected to achieve innovation. Technical/technological product: a conclusive technical report was presented that analyzes the alignment of knowledge management processes and components applied to the specialization course in Police Sciences with the Federal Police's institutional development plan, pointing out options for its greater effectiveness.